METODE DRILL DALAM PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB - Sumiati Sumiati; Nur'ani Aziz (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2019)
This study aims to determine of the mastery of Arabic vocabulary students and also to determine the impact of using the Drill method in Arabic learning to increase Arabic mastery of Nahdlatul Ulum Islamic boarding school students in Soreang, Maros Regency. The research methods used are interviews, observation and documentation to get accurate data and information. The results of this study indicate that the description of Arabic vocabulary mastery in MTs Nahdlatul Ulum Islamic Boarding School in Soreang Maros Regency is considered to be less than optimal because the number of Arabic vocabulary memorization in MTs Nahdlatul Ulum Islamic Boarding School is still lacking and does not yet have the confidence to communicate using Arabic. The Impact of the Implementation of the Drill Method (Exercise) in Improving the Mastery of Arabic Vocabulary in MTs Nahdlatul Ulum Islamic Boarding School in Soreang Maros Regency is considered quite good, where the authors find four indicators as a reference in providing an assessment, namely 1) memorization of Arabic vocabulary quite a lot, 2) there is a habit of using mastered vocabulary in interacting in the school environment, 3) has been able to process some of the vocabulary that is mastered into a simple sentence, 4) has been able to apply Arabic in the mobile phone presentation menu, and 5) Streamlining the reading of the Kitab Kuning.Keywords: Drill Method, Vocabulary